Potensi Gulma Siam (Chromolaena odorata L.) sebagai Bahan Kompos untuk Pengembangan Bawang Merah Organik - Nugroho, Bambang; Mildaryani, Warmanti; Candra Dewi, dan Sri Hartati (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2019)
Siam weed growing in any locations can be used for developing organic agriculture in Indonesia. The research was to find the quantitative and qualitative potential of siam weed as compost material for organic shallot cultivation. This study was descriptive-quantitative research using survey method done in four regencies in Yogyakarta Special Province and laboratory analysis. Purposive random sampling was used in survey method to determine the samples by applying random sampling and nested design. Laboratory analysis was to know nutrient content of siam weed. Shallot was planted using siam weed compost of 10 and 20 ton ha-1, inorganic fertilizer of 500 kg NPK Mutiara 16-16-16 ha-1 and the control. Siam weed was potential for developing organic shallot in Indonesia. Siam weed produced fresh biomass of 80 ton ha-1 with the population density of 24-37 individual m-2 and spread over almost all locations in Yogyakarta Special Province. Siam weed also contained higher nutrients of 2.56% N, 0.38% P, and 2.41% K with C/N ratio of 19.52 under the critical point of 30 so that easy to mineralized. The use of siam weed compost stimulated leaf number on shallot at 7 weeks after planting compared to the use of inorganic fertilizer and the control, but gave no significant yield of 19.71, 15.56, and 18.92 ton ha-1 of bulb, respectively.Keywords: organic fertilizer, development, nutrient